Glycyrrhizinate Monoammonium Cysteine-Loaded Lipid Nanoparticles Allow for Improved Acute Liver Injury Therapy - Yunjie Xu; Pinghui Li; Shiran Sun; Yulin Chen; Lixia Feng; Dawei Jiang; Chidan Wan; Jianbo Li; Xiong Cai (Pharmaceutics)
Background: Acute liver injury (ALI) is a prevalent and potentially lethal condition globally, where pharmacotherapy plays a vital role. However, challenges such as rapid drug excretion and insufficient concentration at hepatic lesions often impede the treatment’s effectiveness. Methods: We successfully prepared glycyrrhizinate monoammonium cysteine (GMC)-loaded lipid nanoparticles (LNPs) using high-pressure homogenization. The characterization and safety of the LNPs were measured using electrophoretic light scattering (ELS), transmission electron microscopy (TEM), dynamic light scattering (DLS), cytotoxicity assays, and hemolysis tests. The distribution of LNPs in mice was explored using fluorescence labeling methods. The encapsulation efficiency of LNP-GMC was detected using High-Performance Liquid Chromatography (HPLC), and its slow-release effect on GMC was assessed through dialysis. The therapeutic effects of LNP-GMC and pure GMC on the ALI model were evaluated using fibroblast activation protein inhibitor (FAPI) PET imaging, blood biochemical indicators, and liver pathology slices. Results: The encapsulation of GMC in LNPs enhances drug stability and prolongs its hepatic retention, significantly improving its bioavailability and sustained release within the liver. This study also explores the expression of fibroblast activation protein (FAP) in ALI, employing 68Ga-FAPI PET/CT imaging for effective differentiation and assessment of liver injury. Conclusions: Our results suggest that LNPs offer an enhanced therapeutic approach for ALI treatment, reducing the required drug dosage, and 68Ga-FAPI PET/CT imaging provides a novel method for diagnosis and treatment assessment. This study contributes valuable insights into the utilization of LNPs in liver disease treatment, presenting a promising direction for future clinical applications.